Application of fuzzy logic for diabetes monitoring / Ag Mohd Fathi Fawwaz Ag Mohd Tahir - Ag Mohd Fathi Fawwaz, Ag Mohd Tahir (2018)
Diabetes is one of the most dangerous disease in the world; by 2025, at least 300 million people will have diabetes. The main objective of this research project is to apply fuzzy logic system for the purpose of monitoring diabetic patient’s blood glucose level. The fuzzy logic system for monitoring blood glucose level was developed by using Matlab’s fuzzy inference system editor. For this project, two input variables and one output variables with 12 linguistic rules were implemented to develop the fuzzy logic for diabetic monitoring. The data obtained from the system is then compared with the real condition. Based on the comparison done for this project, fuzzy logic system shows a promising potential to be used as a control strategy in monitoring patient’s blood glucose level; the percent accuracy for the fuzzy logic system is 83%. In the future, the system can be integrated with blood glucose monitoring device and insulin pump; the combination is called artificial pancreas. With the advent of machine learning, the system can be further improved for benefits of diabetic patient.